Physiotherapeutic intervention in cardiorespiratory emergencies - Yuki Loporchio Ogawa, Kamila; Biglia Frigeri, Larissa; Spoldari Diniz, Jaqueline; Sant’Anna Ferreira, Claudia Adriana (O Mundo da Saúde, 2009)
Emergency services are patients first contact with hospitals. The first Physiotherapy service in this area began at Hospital São Paulo - UNIFESP in 2007. The work of physiotherapists in this sector provides an efficient and faster help, reducing intubation time, mechanical ventilation; respiratory complications, reducing the time of hospital internment. The objective of this study was to evaluate the frequency of physiotherapeutic care in emergency unity of a public hospital, to analyze procedures carried through, the profile of cared patients, and the time of permanence in the sector as well as patients evolution. It was a prospective, transversal and observational study carried through from May to June /2009, in which the patients who entered in the Service of Emergency of São Paulo Hospital - UNIFESP with pulmonary and cardiovascular problems were observed. This study was approved by the Ethics and Research Committee of University Center São Camilo, Process 054/09. 192 patients were evaluated with an average age of 65 (18) years, being 51% female; the most frequent diagnostic was precordialgia in 35 (18%) cases, pneumonia in 29 (15%) cases and congestive cardiac failure in 20 (10%) cases. Most patients (64%) remained less 24-hour in the emergency room. From the 192 patients, 109 (57%) had physiotherapeutic care, 77 patients (40%) needed oxigenotherapy, 24 (12.5%) invasive mechanical ventilation, 34 (18%) had not used invasive ventilation, 50 patients (26%) had received respiratory physiotherapy, 83 (43%) had not been submitted to physiotherapy and 30 (15.5%) had been submitted to orotracheal intubation. As regards evolution, we observe that 35% had been transferred to the ICU, 29% for the infirmary, 25% were discharged from the hospital and 11% died. Considering these data we may conclude that physiotherapeutic care in emergency sectors is still rare, although there is a great demand of patients with serious respiratory and cardiovascular problems that may benefit from this specialty, making it an important area to be explored.